The Russian daily press, 1978-2003 : Political argumentation and the problematic public sphere - Von Seth, Rutger (Russian Journal of Communication, 2013)
The language of newspapers in the public sphere has a crucial impact on how the public perceives and participates in society. It can serve to encourage or counteract active and informed citizens; in fact, it is a crucial element in democratisation processes. The purposes of the present study are to elucidate what means of persuasion are used to support theses on politics in newspaper discourse during both the Soviet and the post-Soviet times; and to discuss the possible social implications that potential changes in modes of argumentation may have for the audiences’ relations to the political system. Public sphere theory and critical discourse analysis comprise the theoretical framework. The article examines transformations in newspaper article texts during a politically critical time span: 1978-2003. As the period under analysis comprises the pre-perestroika, perestroika, and the post-Soviet periods, the analysis is aimed at identifying linguistic features that may be potentially characteristic to the three periods. Rhetorical and logical-pragmatic argumentation analysis is performed on the sample articles in order to identify, map, and interpret patterns of argumentation. The findings imply that, although post-Soviet journalism faces considerable difficulties, a cultural foundation for citizen participation in Russia has been laid through changes in press language.
Keywords: Argumentation analysis; Citizen roles; Public sphere; Soviet/post-Soviet newspapers